2022
DOI: 10.3390/ijerph19074019
|View full text |Cite
|
Sign up to set email alerts
|

Do Managerial Ties Help or Hinder Corporate Green Innovation? The Moderating Roles of Contextual Factors

Abstract: Green innovation has significant implications for firms’ financial, environmental, and social performance. However, its externalities may inhibit the proactive involvement of firms in such initiatives. In this study, we examined the roles of two types of managerial ties (i.e., business and political) in green innovation and further investigated the moderating effects of two types of contextual factors (i.e., environmental regulations and competitive intensity). By conducting an empirical study using survey dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…However, local firms have little incentive to undertake green innovation activities due to the externalities of environmental behavior [11][12][13]. On the one hand, local enterprises pay no cost for the extraction of natural resources; on the other hand, the benefits of environmental management and green innovation undertaken by local enterprises are shared by all economic parties, while the costs are borne alone [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, local firms have little incentive to undertake green innovation activities due to the externalities of environmental behavior [11][12][13]. On the one hand, local enterprises pay no cost for the extraction of natural resources; on the other hand, the benefits of environmental management and green innovation undertaken by local enterprises are shared by all economic parties, while the costs are borne alone [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated inconsistent findings on the business ties-innovation relationship. For instance, business ties positively affect multiple innovation facets, including green ( Zhang and Wang, 2022 ), process ( Shu et al, 2012 ), and product ( Wu, 2011 ; Shu et al, 2012 ; Sami et al, 2019 ). Others include radical ( Shen et al, 2019 ), exploitative ( Wu and Peng, 2020 ), exploratory ( Su and Yang, 2018 ), and firm (process and product).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it does not affect product ( Sami et al, 2019 ), exploitative ( Wu and Peng, 2020 ), or exploratory innovations ( Su and Yang, 2018 ). Accordingly, the concept exhibited an inverted U-shaped effect on green ( Zhang and Wang, 2022 ) and product innovations ( Wu, 2011 ). Furthermore, Gao et al (2017) concluded with a U-shaped effect of political ties on product innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [47] found through their analysis of Chinese construction companies that the political affiliation of enterprises has a significant positive impact on green innovation. Zhang and Wang [48] found that corporate political ties have an inverted U-shaped relationship with green innovation.…”
Section: Enterprise Green Innovationmentioning
confidence: 99%